A mandatory high tax exclusion for GILTI - Kyle Pomerleau (American Enterprise Institute (AEI), 2025)
At the end of this year, the tax rate on Global Intangible Low-Tax Income (GILTI) is set to rise at the same time as the expiration of the individual provisions of the Tax Cuts and Jobs Act (TCJA). Lawmakers are unlikely to allow these changes to occur. However, simply canceling these scheduled changes would be fiscally irresponsible. The coming fiscal cliff provides an opportunity to evaluate and improve GILTI. One area that deserves close inspection is GILTI's structure as an overall minimum tax on foreign operations. This paper outlines a straightforward reform to GILTI: a mandatory high-tax exclusion. Under current law, corporations can elect to exclude the profits and related foreign taxes that face an effective tax rate above a certain threshold. This reform would make this election mandatory and, as a result, GILTI would only apply to income below the exclusion threshold. This reform would reduce opportunities for tax avoidance and reduce incentives to shift mobile assets to foreign jurisdictions while having a minimal impact on complexity. This reform would raise between 68.5 and 72.9 billion between 2026 and 2035, which could offset the revenue loss of other reforms to the taxation of multinational corporations.
Keywords: 330; global economy; Tax policy; TCJA